NEOTYPIFICATION OF TWO MARASMIELLUS SPECIES (AGARICALES: OMPHALOTACEAE) - Atik Retnowati; Fitria Tisa Oktalira (Floribunda, 2023)
The typification of two species of Marasmiellus is discussed. Since the holotypes of Marasmiellus nugatorius and Marasmiellus pangerangensis did not exist, therefore neotypes of both species are designated here. To aid further identification of those species, a line drawing of macro-micromorphological features is provided.